PERANCANGAN ALAT PRESS SARI JAMU MENGGUNAKAN SISTEM HYDRAULIC KAPASITAS 2 KG - Rahmat, Bagas Subakti; Dewi, Rany Puspita; Budiono, Herru Santosa (POLITALA PRESS, 2025)
The process of making herbal medicine still uses traditional methods for making herbal medicine. One of them is the process of squeezing herbal juice. The semi-automatic herbal juice press tool uses a hydraulic system with AISI 304 material. The results of designing the herbal juice press tool are the design of a press tool with a capacity of 2 kg and has dimensions of length 250 mm, width 250 mm, and height 250 mm. The load on static testing is 100 kg. The von Mises stress value in the frame is 38.23 MPa. The deformation value of the jamu juice press frame is 0.065. The smallest safety factor value for the jamu juice press frame is 5. The von Mises stress value for the jamu juice press tube is 21.057 MPa. The maximum deformation value of the jamu juice press tube is 0.017 mm. The smallest safety factor value for the herbal juice press tube is 9.735.